VALUE DETERMINANTS OF THE INFORMATION SECURITY OF A DEMOCRATIC STATE - Danilyan, Oleg; Dzeban, Aleksander; Kalynovskyi , Yury; Kovalenko , Inna; Melyakova, Julia; Danilyan, Vadim (Revista Inclusiones, 2020)
This article analyses the information security of a modern democratic state in a value dimension. It is argued that spiritual values are a necessary component of strengthening the state’s information security. The purpose of this work is to determine the essential characteristics of value determinants and to identify their taxonomy in the information security system of democratic countries. The ways of strengthening the information sovereignty of the state in the context of global competition and confrontation are analyzed. It is emphasized that the importance of strengthening the spiritual sphere of the state is determined by the widespread use of cyber terrorism, cyber espionage, information and hybrid wars in the modern world. The need for a clear fixation and reproduction of the axiological determinants of the information security of a democratic state is due, first of all, to the fact that one of the directions of information aggression, as a rule, is an active influence on the values of public and individual consciousness: their destruction, substitution, deformation. As a conclusion, it is noted that information is a strategic resource of the state, and the protection of the human and social rights to reliable information constitutes the value imperative of a democratic state. With the development of the information society, the world community is faced with the need to protect information human rights, counter information attacks, and form national information security systems.